A Potential‐Based Boundary Element Implementation for Modeling Multiple Scattering from Local and Nonlocal Plasmonic Nanowires. Issue 3 (8th January 2023) - Mystilidis, Christos; Zheng, Xuezhi; Xomalis, Angelos; Vandenbosch, Guy A. E.
Abstract: A novel boundary element implementation that models multiple scattering of plasmonic nanowires is presented. The modeling is based on potentials and the materials constituting the wires can be local (described by the local response model) or nonlocal (described by the nonlocal hydrodynamic model). The nonlocal hydrodynamic model (HDM) provides an important approximation describing nonclassical effects associated with the collective motion of free electrons in metals. The modeling is challenging as different interface conditions are needed at a boundary which separates 1) a local medium from a local medium; 2) a local ( nonlocal ) medium from a nonlocal ( local ) medium; and 3) a nonlocal medium from a nonlocal medium. The algorithm can address constructs of arbitrary geometry and material composition within the HDM; thus, it becomes a complete numerical tool for exploration of nonlocal nanowires. Fictitious sources are imposed at the boundaries, linking the scattered fields to the imposed sources, and matching the interface conditions at the boundaries. This procedure yields a set of Boundary Integral Equations (BIEs). Then, the BIEs are numerically solved utilizing the Boundary Element Method (BEM). The results from the BEM solver are verified quantitatively and qualitatively showing good agreement in both the near‐ and the far‐field regimes. Abstract : Nonlocality is important in plasmonic nanowires with deep‐nm features. The interaction of light with such wires, which can be composed of local and/or nonlocal media, is modeled by the boundary element method. The modeling agrees well with semi‐analytical solutions for core–shell structures and demonstrates the impact of the nonlocality on the optical response of deep‐nm gapped plasmonic nanowires.